Blood on the river : James Town 1607 - Carbone, Elisa Lynn (Puffin Books, 2007)
Traveling to the New World in 1606 as the page to Captain John Smith, twelve-year-old orphan Samuel Collier settles in the new colony of James Town, where he must quickly learn to distinguish between friend and foe.